2022
DOI: 10.1002/jcb.30231
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cytoplasmic FMR1‐interacting protein 2 (CYFIP2) induces browning in 3T3‐L1 adipocytes via repression of GABA‐BR and activation of mTORC1

Abstract: Obesity and related metabolic disorders are epidemic diseases. Promoting thermogenesis and a functional increase in the browning of white adipocytes may counteract obesity. On the other hand, the molecular mechanism that regulates brown and beige fat-mediated thermogenesis is unclear. This article reports a molecular network led by cytoplasmic FMR1-interacting protein 2 (CYFIP2) that negatively regulates adipocyte browning in white adipocytes. Although the function of CYFIP2 in Fragile X Syndrome (FXS) and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Furthermore, GABA-rich fermented extracts and oolong tea have been shown to lower plasma triglyceride and low-density lipoprotein levels, down-regulate genes related to adipogenesis (SREBP-1c, FAS, SCD-1, and ACC), and promote lipid metabolism and fatty acid oxidation ( Park et al, 2020 ; Weerawatanakorn et al, 2023 ). Noteworthy is the consistent finding across multiple studies that GABA induces adipocyte browning, facilitates beige fat differentiation, and acts as an inhibitor of obesity and associated metabolic disorders ( Manigandan and Yun, 2022 ). Treatment with GABA has been shown to alter the composition of gut microbiota, elevate beige fat content, and ultimately improve metabolic levels in obese mice ( Ma et al, 2023 ).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, GABA-rich fermented extracts and oolong tea have been shown to lower plasma triglyceride and low-density lipoprotein levels, down-regulate genes related to adipogenesis (SREBP-1c, FAS, SCD-1, and ACC), and promote lipid metabolism and fatty acid oxidation ( Park et al, 2020 ; Weerawatanakorn et al, 2023 ). Noteworthy is the consistent finding across multiple studies that GABA induces adipocyte browning, facilitates beige fat differentiation, and acts as an inhibitor of obesity and associated metabolic disorders ( Manigandan and Yun, 2022 ). Treatment with GABA has been shown to alter the composition of gut microbiota, elevate beige fat content, and ultimately improve metabolic levels in obese mice ( Ma et al, 2023 ).…”
Section: Discussionmentioning
confidence: 95%
“…A recent study in cultured cells reported that CYFIP2 is involved in the thermogenesis and regulation of lipid metabolism in white adipocytes, explicitly in uencing the browning of white adipocytes 37 . Other studies reported the possibility of the CYFIP2 locus being associated with diet-induced obesity and metabolic dysfunction in mice 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Through its ability to modulate both the actin cytoskeleton and protein translation, Cyfip2 is well-positioned to be a critical factor for many processes in neurodevelopment [33,34,[37][38][39]45,49]. Further highlighting its importance, Cyfip2 has been implicated in an array of neuropsychiatric and other conditions, including schizophrenia [60], autism [49,[61][62][63], binge eating [64][65][66], obesity [67], amyotrophic lateral sclerosis (ALS) [68,69], Alzheimer's disease [70], epilepsy [63,[71][72][73][74], and cancer [75][76][77][78][79][80]. Here we focused on Cyfip2's role in a common endophenotype of schizophrenia and autism, increased acoustic startle responsiveness [4,24,27,28].…”
Section: Discussionmentioning
confidence: 99%